Kuliah Kerja Nyata Untuk Meningkatkan Partisipasi Masyarakat Dalam Kegiatan Keagamaan di Desa Aek Haruaya Kecamatan Portibi - Ainun Mufidah; Elvina Sari Lubis; Fitriani Fitriani; M.Habiburrohman Al Makky; Nur Atika; Nur Afni; Rahmad Syafii; Rico Alfarisi; Sari Wulan; Zumiah Safitri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The understanding research aims to carry out activities to increase community participation in religius activities. This study uses qualitative researchusing several methods in order to obtain clear or broad information related to research. The results of the study show that comunity partisipation in religious activities can be increased through comunity service. This service is done to instill a sense of social in each member of the KKN group this is very necessary because it is one of the Tri Dharma of Higer Education that must exist in every student. That method used in this research is quqlitqtive method.